Moving Millions Transport Strategies for Sustainable Development in Megacities - Moavenzadeh, F.; Markow, M.J (Alliance for Global Sustainability Bookseries, 2007)
This book has been several years in the making. It has grown out of basic areas of inquiry begun under the auspices of the Alliance for Global Sustainability in the late 1990s, and has culminated with a series of on-site, collaborative studies conducted through AGS in cooperation with of?cials in Guangzhou, People's Republic of China (PRC), during the early 2000s. Many individuals have made important contributions to the ideas, ?ndings, and results that have been compiled in this volume. The authors wish to recognize these signi?cant contributions below. The Alliance for Global Sustainability is an international partnership among four of the leading scienti?c and technological universities worldwide: • The Massachusetts Institute of Technology (MIT-AGS); • The University of Tokyo (UT); • The Swiss Federal Institute of Technology (ETH); and • The Chalmers University of Technology. Created in 1997, the AGS today brings together hundreds of university scientists, engineers, and social scientists to address complex issues that lie at the intersection of environmental, economic, and social policy goals. Since its inception, the AGS has promoted and supported multidisciplinary research teams drawn from its partner institutions. Working on critical issues in sustainability across several ?elds encompassing energy and climate, mobility, urban systems, water and agriculture, cleaner technologies, public policy, and communications, these teams have developed a signi?cant body of new knowledge. Furthermore, A- sponsored teamshave worked withengaged,farsighted leaders of global businesses and industries, governments, and non-governmental organizations (NGOs) to provide innovative but practical solutions to urgent environmental problems worldwide.